2021
DOI: 10.4102/sajhivmed.v22i1.1177
|View full text |Cite
|
Sign up to set email alerts
|

Profile of presentation of HIV-positive patients to an emergency department in Johannesburg, South Africa

Abstract: Background Despite improved availability and better access to antiretroviral therapy (ART), approximately 36% of human immunodeficiency virus (HIV)-positive South Africans are still not virally suppressed. Objective The aim of this study was to describe the patterns of presentation of HIV-positive patients to a major central hospital emergency department (ED). Methods In this prospectively designed study, consecutive HIV-positive patients pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…Among those that were managed in the ED, 1308 were HIV-positive, however, 84 did not consent to study participation. Hence, the final study sample comprised 1224 patients [13][14][15]. The median (IQR) and mean (SD) LOS was 4.6 (2.6-8.2) days and 6.9 (8.2) days, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those that were managed in the ED, 1308 were HIV-positive, however, 84 did not consent to study participation. Hence, the final study sample comprised 1224 patients [13][14][15]. The median (IQR) and mean (SD) LOS was 4.6 (2.6-8.2) days and 6.9 (8.2) days, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the aim of this study was to determine predictors of prolonged hospital stay (LOS �7 days) in HIV-positive patients presenting to the ED. Findings pertaining to other aspects of this study have been published separately [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the largest and most comprehensive single-centre study to have determined predictors of in-hospital mortality in consecutive HIV-positive patients in an ED setting. Findings pertaining to other aspects of this study have been published separately [21]. Although multiple studies have reported on the predictive value of various parameters in HIV-positive patients, most of these studies only reported on a few variables and were predominantly conducted in outpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…Findings pertaining to other aspects of this study have been published separately. [17,18] This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.…”
mentioning
confidence: 99%